THE CREATION OF A DANCE THAT REFLECTS DECEPTIONS IN PERFORMING ARTS THROUGH THE EIGHT ELEMENTS OF ARTISTIC COMPOSITION - Wanna, Ohm; Charassri, Naraphon (Fine Arts Journal: Srinakharinwirot University, 2025)
Background and Objectives: This research titled “The Creation of a Dance that Reflects Deceptions in Performing Arts through the Eight Elements of Artistic Composition” aims to explore the creative process of dance that embodies the theme of deception in performing arts through the eight fundamental elements of artistic creation. Methods: This research study employed qualitative and creative research methods. The research tools included: 1) documentary research, 2) interviews with relevant individuals, 3) media communication, 4) field data surveys, and 5) artist standard criteria. All collected data were then analyzed and applied to the experimental process and creative production. Key Findings: The research presented a model for creating new works in the field of performing arts based on the eight elements of artistic creation: 1) script design using the collage concept, 2) choreography using the concept of post-modern dance, contemporary dance, dance in everyday life, and Thai dance, 3) the performer selection with the researcher playing the main roles, 4) the costume design based on minimalist art and the theory of “less is more,” incorporating elements of everyday attire, 5) sound and music design using natural sounds, 6) performance props design using symbols as an important principle in conveying meaning, 7) performance space design using a location outside the theater 8) lighting design using natural light. Implications of the Study: The research proposed a model for creating dance that reflects deception in performing arts, based on all eight creative elements. The study aims to raise awareness in society regarding the presence of deception in performing arts and the broader art industry, contributing to a critical discourse on authenticity, artistic manipulation, and audience perception. Conclusions and Future Research: This study is a creative work in dance that reflects deception in the performing arts, serving as a framework for developing new dance works that engage with themes of respect and ethical considerations in the creative process across all artistic disciplines.